2019
DOI: 10.1371/journal.pone.0220173
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism is associated with FGFR3 and RAS mutation in non-muscle-invasive bladder cancer

Abstract: Objective TP53 , a well-known tumor-suppressor gene in bladder carcinogenesis, has a functional single-nucleotide polymorphism on codon 72. The aim of this study was to elucidate the association between TP53 codon 72 polymorphism and somatic mutations in bladder cancer. Material and methods Germline TP53 codon 72 polymorphism and somatic mutations of 50 cancer-associated genes were analyzed in 103 blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The flowchart of selecting process and the excluded reasons of studies is integrated in Figure 1. Altogether, 7 researches were incorporated in this meta‐analysis 22‐28 …”
Section: Resultsmentioning
confidence: 99%
“…The flowchart of selecting process and the excluded reasons of studies is integrated in Figure 1. Altogether, 7 researches were incorporated in this meta‐analysis 22‐28 …”
Section: Resultsmentioning
confidence: 99%
“…The abundant GPNMB protein levels tended to be higher in the MIBC patients ( n = 31/40) than in the NMIBC patients ( n = 27/55), and GPNMB expression was also higher in high‐grade ( n = 43/63) than in low‐grade ( n = 15/32) tumors (Figure 1a and Table 1). In addition, GPNMB protein expression was correlated with TP53 mutation status 28 in all the patients ( p = 0.031, Table 1) but not in the NMIBC or the MIBC patients, respectively. While the expression level of GPNMB protein was shown to affect only NMIBC prognosis (Figure 1b–d), univariate and multivariate analyses showed high GPNMB expression to be associated with recurrence of NMIBC (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…For the analysis, we used multicenter cohort data from 144 patients with clinically diagnosed urothelial carcinoma from several institutions with approval from the ethics committee of the University of Tsukuba Hospital (approval number: H25-116). 27,28 We used tissue microarrays of the primary cancer tissue samples of 55 patients with NMIBC and of 40 patients with MIBC after excluding the cases without complete clinical data or histological evaluations. The tumors were staged according to the seventh edition of the UICC TNM classification system.…”
Section: Clinical Samplesmentioning
confidence: 99%
“…A study by Nanda et al[ 15 ] identified 11.67% tumors which harbored K-Ras mutations as well as a significant correlation of the K-Ras mutant status with the smoking history of patients, high tumor grade, lymph node involvement and tumor recurrence. Yan et al[ 31 ] reported the ability of mutant K-Ras , but not H-Ras , to confer metastatic phenotype in cells by interfering with the maturation of cell surface integrins and disrupting cell-cell adhesion. A recently published study reported a higher prevalence of point mutations in all the Ras isoforms in NMIBC (27%) compared to MIBC (9.4%) patients.…”
Section: Discussionmentioning
confidence: 99%